Bibliometric analysis of reward-based crowdfunding using VosViewer - Jie, Gao; Senik, Rosmila; Haji Yahya, Mohamed Hisham; Abdullah, Amalina (Zhongguo Hangtian Gongye Zonggongsi, 2023)
In the context of the global COVID-19 pandemic spanning from 2019 to 2022, small and medium-sized enterprise entrepreneurs, as well as individual entrepreneurs, encountered significant challenges in securing financing. However, with the rapid rise of online crowdfunding platforms, these entities are increasingly turning to crowdfunding to raise funds. As a result, research on crowdfunding through the Internet has grown, although the number of comprehensive reviews on this topic remains limited, leading to a lack of a holistic understanding of crowdfunding. To address this research gap, this paper conducts a comprehensive review of the existing literature on online crowdfunding. The aims of the paper is through the application of vosviewer software to reveal the research direction and research hotspots in the field of product crowdfunding research. The study examines literature published between 2009 and 2022 from the Scopus database, focusing on sources with relevant correlations. Through a systematic search in the Scopus database, publication trends, the number of relevant articles, and influential authors in the crowdfunding field are analysed. Furthermore, the study utilizes VOS Viewer to perform a literature visualization and econometric analysis, allowing the identification of pertinent research topics within crowdfunding. Co-citation analysis is applied to construct a correlation network graph, providing insights into the distribution patterns of crowdfunding-related literature. By undertaking this review and analysis, the paper aims to enhance the overall understanding of crowdfunding and its implications for small and medium-sized enterprises, as well as individual entrepreneurs, during the challenging years of the COVID-19 pandemic. The findings are expected to contribute to the existing body of knowledge on crowdfunding and shed light on potential avenues for future research in this evolving field.